ANÁLISIS OSTEOLÓGICO DE UNA MUESTRA DE LA POBLACIÓN YCHSMA DEL SITIO ARQUEOLÓGICO DE ARMATAMBO, SECTOR 22 DE OCTUBRE - Aguayo Franco, Adriana (2008)
This work presents archaeological and osteological evidences of the investigation made in the site of Armatambo, which have allowed to define, in the osteological case, the pathological conditions of a sample from the Middle Ychsma population corresponding to the 22 de Octubre sector, also joining the associated objects belonging to each Funeral Context. The results show a significant bony alteration in all the analyzed individuals. This high osteopathological percentage would reflect a significant preponderance in types of labor activity and extreme violence in which their members lived.